Analysis of Readiness For Implementation of Electronic Medical Records Using DOQ-IT Method - Widiyanto, Wahyu Wijaya; Sulistyati, Hanifah Shobri; Zahroh, Salsabila Ummu (Institut Teknologi Bisnis AAS Indonesia, 2023)
This study addresses the challenge of managing medical records in Indonesia’s health sector, particularly focusing on the transition to electronic medical records (RME) as mandated by PMK No. 24 of 2022. The primary objective is to assess the readiness for implementing Electronic Medical Records (EMR) at the Milla Husada Clinic using the DOQ-IT (Doctor’s Office Quality-Information Technology) Approach. The research adopts a descriptive design with a quantitative approach, utilizing questionnaires to gather data from 40 clinic officers. Total sampling technique was employed for participant selection. Univariate analysis was used for data interpretation. The findings reveal a high level of readiness for RME implementation at the clinic, with a total readiness score of 117.74, placing it in range III, indicative of a very ready status. The readiness levels, in descending order of scores, were: organizational work culture (4.34), governance and leadership (4.26), IT infrastructure (4.23), and human resource readiness (3.80). Despite the overall readiness, the study identifies human resources as an area requiring further enhancement, specifically the need for specialized training in RME implementation. This research highlights the critical areas for improvement to ensure successful adoption of electronic medical records in the healthcare setting.